2022
DOI: 10.3390/ijms23126812
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Milk Extracellular Vesicles on Colorectal Cancer

Abstract: Colorectal cancer remains one of the leading prevalent cancers in the world and is the fourth most common cause of death from cancer. Unfortunately, the currently utilized chemotherapies fail in selectively targeting cancer cells and cause harm to healthy cells, which results in profound side effects. Researchers are focused on developing anti-cancer targeted medications, which is essential to making them safer, more effective, and more selective and to maximizing their therapeutic benefits. Milk-derived extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 187 publications
0
21
0
Order By: Relevance
“…HMEVs also harbor functional molecules with anti-tumor and anti-viral effects, e.g., lactadherin which can inhibit rotavirus [ 92 ] and miR-148a-3p which inhibits gastric and pancreatic cancers [ 109 , 110 ]. The therapeutic potential of bovine milk-derived EVs, including those EVs loaded with miR-148a-3p, have been investigated in colon cancer [ 209 , 210 ]. Future preclinical and clinical studies should evaluate the safety and efficacy of hMEV-based therapy against NEC, rotavirus infection, and adult gastrointestinal cancers.…”
Section: Challenges and Clinical Implicationsmentioning
confidence: 99%
“…HMEVs also harbor functional molecules with anti-tumor and anti-viral effects, e.g., lactadherin which can inhibit rotavirus [ 92 ] and miR-148a-3p which inhibits gastric and pancreatic cancers [ 109 , 110 ]. The therapeutic potential of bovine milk-derived EVs, including those EVs loaded with miR-148a-3p, have been investigated in colon cancer [ 209 , 210 ]. Future preclinical and clinical studies should evaluate the safety and efficacy of hMEV-based therapy against NEC, rotavirus infection, and adult gastrointestinal cancers.…”
Section: Challenges and Clinical Implicationsmentioning
confidence: 99%
“…Exosomes derived from bovine milk were used for the oral delivery of PAC and 5-FU; exosomes are considered an emerging drug-delivery technology described in recent times [ 23 , 24 ]. Exosomes are the biological nanoparticles present in all biological fluids, whose sizes range from 30 to 150 nm and have pulled an impressive consideration as a drug delivery system [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have confirmed that milk-derived exosomes can be absorbed by a variety of cells [ 89 , 119 ] and can be used as delivery vehicles for short interfering RNA (siRNA), miRNA, and drugs [ 120 , 121 ]. The antiviral activity [ 122 ], anti-inflammatory activity [ 123 , 124 , 125 ], and the anticancer activity [ 126 , 127 ] of milk-derived exosomes have also been characterized through experiments. Several groups have compared the functional activity of bovine, buffalo, goat, and yak milk-derived exosomes [ 128 , 129 , 130 , 131 ].…”
Section: Application Prospects Of Exosomes As Drug Delivery Vehicles ...mentioning
confidence: 99%